Congenital Corneal Endothelial Dystrophies Resulting From Novel De Novo Mutations. Issue 2 (February 2016) - Cunnusamy, Khrishen; Bowman, Charles B.; Beebe, Walter; Gong, Xin; Hogan, R. Nick; Mootha, V. Vinod
Abstract : Purpose: To describe 2 cases of congenital corneal endothelial edema resulting from novel de novo mutations. Methods: Case A patient was a 15-month-old white child and case B patient was a 3-year-old Hispanic child presenting with bilateral cloudy corneas since birth. Clinicopathologic findings are presented. DNA samples were screened for mutations in candidate genes by Sanger sequencing. Results: Slit-lamp examination of case A patient revealed stromal edema and haze. Histology of the keratoplasty button showed stromal thickening with loss of endothelium and thin Descemet membrane. Sanger sequencing established the diagnosis of congenital hereditary endothelial dystrophy by detection of a compound heterozygous mutation in SLC4A11 . The proband displayed a novel de novo frameshift mutation in one SLC4A11 allele, p.(Pro817Argfs*32), in conjunction with a maternally inherited missense mutation in SLC4A11, p.(Arg869His). Case B patient similarly presented with stromal edema and stromal haze. Histopathologic analysis revealed a spongy epithelium, focal discontinuities in Bowman layer, stromal thickening with areas of compacted posterior stroma, variable thickness of Descemet membrane, and regional multilayered endothelium. Sanger sequencing found a novel de novo nonsense mutation in the first exon of ZEB1, p.(Cys7*). Conclusions: To the authors' knowledge, we report the earliest clinical presentation of posterior polymorphous corneal dystrophy resulting from a de novo mutation in ZEB1 . Additionally, we present a congenital hereditary endothelial dystrophy case with a thin Descemet membrane with a novel compound heterozygous SLC4A11 mutation. In the absence of a family history or consanguinity, de novo mutations may result in congenital corneal endothelial dystrophies.